Research, records and responsibility: ten years of PARADISEC - Harris, Amanda; Thieberger, Nick; Barwick, Linda (Sydney University Press, 2015)
The Pacific and Regional Archive for Digital Sources in Endangered Cultures (PARADISEC) has been on the cutting edge of digital archiving, building a significant historical collection and community of practice engaged in the preservation and accessibility of research materials. Over the ten years of PARADISEC's operation, the repository has grown to represent over 860 languages from across the world, including cultural materials from the Pacific region and South-East Asia, North America, Africa and Europe. With over 5000 hours of audio, the extent of the archival material, as well as the inclusion of a variety of styles such as songs, narratives and elicitation, has resulted in an invaluable resource for researchers and communities alike. PARADISEC's innovation in archival practice allows communities to access original recordings of their own cultural heritage, and provides fieldworkers with a wealth of primary material. Research, Records and Responsibility explores developments in collaborative archiving practice between archives and the communities they serve and represent, incorporating case studies of historical recordings, visual data and material culture. It brings together the work of Australian and international scholars commemorating ten years of PARADISEC, and reflects on the development of research and language archiving.